Evaluation of the Solid Dispersion System Engineered from Mesoporous Silica and Polymers for the Poorly Water Soluble Drug Indomethacin: In Vitro and In Vivo - Xi, Ziyue; Zhang, Wei; Fei, Yali; Cui, Mingshu; Xie, Luyao; Chen, Lu; Xu, Lu (Pharmaceutics, 2020)
This work explored absorption efficacy via an in vivo imaging system and parallel artificial membrane penetration in indomethacin (IMC) solid dispersion (SD) systems. Two different polymer excipients—hydroxypropyl methylcellulose (HPMC) and Kollicoat IR as precipitation inhibitors (PIs)—combined with mesoporous silica nanoparticles (MSNs) as carriers were investigated. The IMC–SDs were prepared using the solvent evaporation method and characterized by solubility analysis, infrared (IR) spectroscopy, powder X-ray diffraction (PXRD), field emission scanning electron microscopy (FESEM), and differential scanning calorimetry (DSC). It was confirmed that IMC successfully changed into an amorphous state after loading into the designed carriers. The in vitro release and stability experiments were conducted to examine the in vitro dissolution rates of IMC–SDs combined with HPMC and Kollicoat IR as PIs which both improved approximately three-fold to that of the pure drug. Finally, in vivo studies and in vitro parallel artificial membrane penetration (PAMPA) experiments ensured the greater ability of enhancing the dissolution rates of pure IMC in the gastrointestinal tract by oral delivery. In brief, this study highlights the prominent role of HPMC and Kollicoat IR as PIs in MSN SD systems in improving the bioavailability and gastrointestinal oral absorption efficiency of indomethacin.